The role of serial right heart catheterization in risk stratification and management of pulmonary arterial hypertension. (3rd July 2022) - Sharma, Dikshya; Shah, Ravi J; Sreenivasan, Jayakumar; Kafle, Paritosh; Gupta, Rahul; Levine, Avi; Lanier, Gregg M.; Aronow, Wilbert S.
ABSTRACT: Introduction: Pulmonary arterial hypertension (PAH) is characterized by elevated pulmonary arterial blood pressure secondary to increased pulmonary vascular resistance. Areas covered: Invasive hemodynamic assessment by heart catheterization (RHC) remains the gold standard to confirm the diagnosis, to determine the severity of right ventricular dysfunction and to test for pulmonary vasoreactivity. After diagnosis and initiation of therapy, many PAH centers continue to perform RHC at regular intervals to monitor for disease progression and alter management. We discuss the importance of risk stratification in PAH, the role of RHC in the evaluation and treatment of these patients and compare non-invasive risk assessment tools to that of RHC. Expert opinion: RHC is useful for diagnosis of PAH, assessing the risk of mortality and morbidity, directing the escalation and de-escalation of therapy, and monitoring for disease progression. In the current era of improved non-invasive cardiac hemodynamic assessment, the role for routine follow-up serial RHC in patients with PAH needs to be reassessed in future studies. With the availability of non-invasive risk assessment tools such as REVEAL Lite 2, it may be reasonable to reconsider the role of annual or protocoled RHC, and instead, move on to an "as needed" and individual approach.